The use of space in relation to contemporary dining patterns and practices of selected lower middle-income Filipino families - Patoc, Cristina F.
The study sought to determine whether or not the dining spaces in the residences of selected lower-middle income families have traditional functions as before. A total of ten (10) respondent families from Paranaque City were included in the study. A qualitative approach of research using in-depth interview, interview guide and observation aided by photographs was used to carry out the study. According to the findings of this study, the dining tables among respondent families were seldom used for their traditional function, which is primarily used for eating. Instead, it was found to serve other utilitarian purposes such as a study area, storage for leftover food, condiments and containers or as a buffet table where families serve their food. The findings showed the living area as an emerging alternative dining space. The study demonstrated how the living area became an example of a dynamic space serving various functions for the needs of the families. It was seen as a place for socializing and entertaining guests, studying, watching television, sleeping and an alternative space for dining as well. It was also where families find therapy or a sense of relaxation mainly because of the presence of the television there. They find themselves entertained after a long day from school or work. The study established that the dining spaces in the residences of selected lower-middle income families no longer serve their traditional function.